Evidence of taxonomy for Developmental Topographical Disorientation: Developmental Landmark Agnosia Case 1. Issue 2 (3rd April 2019) - Piccardi, L.; De Luca, M.; Di Vita, A.; Palermo, L.; Tanzilli, A.; Dacquino, C.; Pizzamiglio, M. R.
ABSTRACT: We report Developmental Landmark Agnosia (DLA) in a 6-year-old boy (L.G.) who was referred to us for congenital prosopagnosia (see Pizzamiglio et al., 2017, in which both testing and rehabilitation of Congenital Prosopagnosia are reported). We investigated his performance using a neuropsychological battery and eye movement recordings. The assessment showed the presence of deficits in recognizing familiar places (along with Congenital Prosopagnosia), but not common objects. Eye movement recordings confirmed his problems in recognizing familiar landmarks and misrecognition of unfamiliar places. L.G. is the first evidence of a DLA, suggesting identification of taxonomy of navigational disorders in Developmental Topographical Disorientation is possible, as in the Acquired Topographical Disorientation.